2011
DOI: 10.1007/s00442-011-2066-1
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal colonization does not affect tolerance to defoliation of an annual herb in different light availability and soil fertility treatments but increases flower size in light-rich environments

Abstract: Heterogeneous distribution of resources in most plant populations results in a mosaic of plant physiological responses tending to maximize plant fitness. This includes plant responses to trophic interactions such as herbivory and mycorrhizal symbiosis which are concurrent in most plants. We explored fitness costs of 50% manual defoliation and mycorrhizal inoculation in Datura stramonium at different light availability and soil fertility environments in a greenhouse experiment. Overall, we showed that non-inocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Honey bee flower probing rates were significantly reduced on plants that had been inoculated with single species of AMF compared to non-mycorrhizal controls; this is surprising given that AMF usually increase floral reward and pollinator preference (Gange and Smith, 2005; Gange et al, 2005; Aguilar-Chama and Guevara, 2012). Lepidoptera flower probes were significantly greater for mixture plants than single species inocula plants combined, suggesting that the three AMF had interactive effects on floral traits that increased Lepidoptera preference.…”
Section: Discussionmentioning
confidence: 96%
“…Honey bee flower probing rates were significantly reduced on plants that had been inoculated with single species of AMF compared to non-mycorrhizal controls; this is surprising given that AMF usually increase floral reward and pollinator preference (Gange and Smith, 2005; Gange et al, 2005; Aguilar-Chama and Guevara, 2012). Lepidoptera flower probes were significantly greater for mixture plants than single species inocula plants combined, suggesting that the three AMF had interactive effects on floral traits that increased Lepidoptera preference.…”
Section: Discussionmentioning
confidence: 96%
“…In the few studies of AMF effects on plant tolerance (here used to denote equal growth or fitness under conditions of herbivore damage), AMF increased plants' ability to tolerate herbivore damage in some cases (e.g., Frank et al 2003), while others showed little or no effect (Borowicz 1997;Gange et al 2002;Bennett and Bever 2007;Varga et al 2009;Aguilar-Chama and Guevara 2012;González et al 2015), and still others showed that AMF reduced tolerance (Bennett and Bever 2007;Garrido et al 2010). These mixed results may be due to one or more of several factors.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%